Frailocracy in the Philippines - Del Pilar, Marcelo H. 1850-1896 (National Historical Institute, 1979)
"The La Frailocracia Filipina was an answer to a pamphlet entitled Los Frailes en Filipinas which was written by a Spaniard. The arguments were in five parts, namely, the much-mooted problem of filibusterims, the much-vaunted love of the friars for Spain, the disparagement of Filipino civilization by the friars, the influence of the friars on the Filipinos, and the aspirations of the Filipino."--P. viii.